Bangladesh : Poverty Reduction Strategy Paper Status Report. (IMF Staff Country Reports; Country Report, 2004)
This paper presents the status report on Bangladesh's Poverty Reduction Strategy Paper (PRSP). Having prepared the Interim-PRSP (I-PRSP) in March 2003, the government of Bangladesh has set itself to a well-rounded process of preparing the full-blown PRSP by December 2004. That would entail a time span of 21 months compared with the average time of about 26 months reported to have been required by the I-PRSP countries to complete their full PRSPs. The government adheres to the core principles of the PRSP that it should be country-driven, results-oriented, comprehensive in scope, partnership-oriented, and fully participatory in nature.